UARS Microwave Limb Sounder observations of dentrification and ozone loss in the 2000 Arctic late winter - Santee, M. L.; Manney, G. L.; Livesey, N. J.; Waters, J.W. (2004)
The UARS Microwave Limb Sounder obtained measurements of CIO, HNO3, and O-3 inside the Arctic lower stratospheric vortex during two intervals in February and March 2000. The data show evidence of significant chemical processing in February, consistent with the exceptionally cold conditions that prevailed earlier in the winter.